Nutritional Needs of the Female Athlete: Risk and Prevention of Low Energy Availability. Issue 4 (August 2020) - Black, Katherine E.; Baker, Dane F.; Sims, Stacy T.
Abstract : ABSTRACT: To date, most of the research surrounding low energy availability (LEA) and female athletes has focused on the high prevalence rates (2–77%). Despite the severe negative health and performance consequences, awareness of this issue is low. There are potentially a multitude of factors that contribute to the development of LEA across the menstrual cycle and training phases. This review highlights these influences and provides practical tips for those working with female athletes.